The future of ESDP in the wake of the negative referenda - Ulrich Petersohn; Sibylle Lang (Stiftung Wissenschaft und Politik (SWP), 2005)
The failure of the referenda on the European Constitutional Treaty (ECT) in France and the Netherlands has shown that the political aims of the European heads of state and government do not tally with the desires of the electorate. This has uncovered a crisis in European integration: it currently does not seem possible to proceed with integration in the way envisaged by political decision-makers. The rejection of the ECT could also have an impact on policy areas which citizens want to see become more integrated. This applies to a certain extent to the European Security and Defence Policy (ESDP), which has enjoyed a very high level of citizen approval since it was introduced in the late 1990s. Is the acceptance of the ECT an essential prerequisite for the further devel-op-ment of the ESDP? What impact might the crisis in European integration have on the ESDP? (SWP-Comments / SWP)
Keywords: 320